Acupuncture for Treatment of Arthralgia Secondary to Aromatase Inhibitor Therapy in Women with Early Breast Cancer: Pilot Study. Issue 3 (September 2013) - Oh, B; Kimble, B; Costa, D S J; Davis, E; McLean, A; Orme, K; Beith, J
Background: Aromatase inhibitors (AIs) are recommended as adjuvant hormone treatment for postmenopausal women with early breast cancer. A substantial proportion of women taking AIs experience joint pain and stiffness. Studies have suggested that acupuncture may be effective in treating joint pain. Objective: A pilot study was conducted to evaluate the feasibility, safety and efficacy of using acupuncture to treat AI-induced arthralgia. Methods: A total of 32 patients were randomised to receive either sham or real electroacupuncture (EA) twice weekly for 6 weeks. Outcomes of joint pain, stiffness and physical function were measured with the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), overall pain severity and interference with the BPI-SF and quality of life (QOL) with the Functional Assessment of Cancer Therapy-General (FACT-G) instrument. Hand strength was assessed by a grip test, and a serum marker of inflammation (C reactive protein (CRP)) was also measured. All assessments were performed at baseline, 6 weeks and 12 weeks, except for blood samples at baseline and 6 weeks only. Results: No serious adverse events were reported during or after acupuncture treatments. There were no significant differences in outcome measures. However, positive trends were observed in stiffness and physical function at week 12 in favour of real EA. Conclusions: Findings suggest that acupuncture is feasible and safe in patients with breast cancer with joint pain caused by AI. A larger study with adequately powered to confirm these results and detect clinically relevant effects is needed.